How Do Primary School Students Perform? Fundamental Movement Skills for Throwing Catch Baseball - Ediwitoko, Rachmad; Hasmyati, Hasmyati; Asran, Asran (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The issue in this research is that students struggle to move because they lack fundamental throwing and catching mobility skills. There are still many students who look stiff and need the teacher's assistance to move in accordance with the teacher's instructions, even though some students are less able to practice throwing and catching balls, even though some students can already do so. The purpose of this study was to determine the level of fundamental movement skills for throwing and catching a baseball in primary school. The sample of this research is class III MIS AL Qosimy Watu Galuh, totaling 25 people. Data collection techniques using a t-test: The P value obtained is less than 0.05, which is 0.00. In the catch test, the test statistic results show the P-value obtained is less than 0.05, which is 0.00, with an average value of 34.54. The results of the test statistic on the throwing and catching values show that the P-value obtained is less than 0.05, which is 0.00. So it can be concluded that the throwing value of the students is equal to 15 with an average value of 11.5. The results of the overall analysis show that the components of the throw, catch, and throw catch scores of each student are not the same as the expected target value.